Motivation and substance use outcomes among adolescents in a school-based intervention. (February 2016) - Serafini, Kelly; Shipley, Leandra; Stewart, David G.
Abstract: The stages of change (Precontemplation, Contemplation, Preparation, Action, and Maintenance) have been well studied in adult populations. However, fewer studies have examined how the stages of change are related to adolescent substance use. Furthermore, there have been no studies that have examined how the stages of change relate to outcomes in a school-based intervention. To better capture adolescent motivation, we added an additional group to the Transtheoretical Model of Change, which we titled Coerced Action, to represent adolescents that made changes to their substance use despite low problem recognition (representing the internal motivation of Precontemplation and the change behaviors of the Action group). We then examined how the stages of change were related to a thorough assessment of substance use at baseline and corresponding treatment outcomes. Our sample consisted of 264 adolescents (mean age: 16.1, 44.5% Caucasian, 37.5% female) who participated in an 8-week, school-based Motivational Enhancement intervention. Results indicated significant group differences across the stages of change in substance use patterns (alcohol use, negative consequences, affective dysregulation), as well as treatment outcomes (alcohol use and negative consequences). For instance, adolescents in the Action group demonstrated more negative consequences at 16 weeks follow-up than those in Precontemplation and Coerced Action, F (1, 3) = 8.23, p  < .001. The Coerced Action group reported the most alcohol use at 16 weeks follow-up, although the finding was not significant when post-hoc tests were conducted. This study provides meaningful support for the assessment of motivation among adolescent substance users within school-based settings. Highlights: The Transtheoretical Model of Change was applied to an adolescent sample. A new group, Coerced Action, was added to the model. The Coerced Action group had a similar trajectory as those in Precontemplation.